Expression of fungal cellulase gene in Lactococcus lactis to construct novel recombinant silage inoculants - Ozkose, E; Akyol, I; Kar, B; Comlekcioglu, U; Ekinci, M S (Folia microbiologica, 2009)
The facultative anaerobic bacterium Lactococcus lactis has been used as a host for expression of a gene isolated from the anaerobic rumen fungus Neocallimastix sp. The coding region of the cellulase gene was obtained from the fungus with the aid of polymerase chain reaction amplification. The gene was then transformed into pCT vector system and the constructed recombinant plasmid was introduced into two L. lactis strains (IL403 and MG1363) by electroporation. The gene encoding the fungal originated cellulase was expressed in both strains successfully although the expression level was relatively lower in comparison with the original enzyme activity. Genetically modified L. lactis strains were used as silage inoculants for pre-biodegradation of the plant biomass during ensiling. That treatment resulted in a notable reduction of the acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents of the plant biomass used as silage material. Inoculation with recombinant strain IL1043 resulted in 4.8 and 9.7 % decrease in NDF and ADF contents, respectively while the inoculation of silage with strain MG1363 decreased the ADF content by >5 %.
Keywords: Cellulase; Gene Expression; genetické inženýrství; Silage; Genetic Engineering; exprese genu; fungální proteiny; Neocallimastix; Fungal Proteins; celulasa; Lactococcus lactis; siláž